2017
DOI: 10.1016/j.neuropharm.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Rat animal models for screening medications to treat alcohol use disorders

Abstract: The purpose of this review is to present animal research models that can be used to screen and/or repurpose medications for the treatment of alcohol abuse and dependence. The focus will be on rats and in particular selectively bred rats. Brief introductions discuss various aspects of the clinical picture, which provide characteristics of individuals with alcohol use disorders (AUDs) to model in animals. Following this, multiple selectively bred rat lines will be described and evaluated in the context of animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 639 publications
(494 reference statements)
1
55
2
2
Order By: Relevance
“…Various studies with rats, mostly employing chronic choice drinking paradigms [e.g. 36;37;28 ] showing positive effects of acamprosate on alcohol drinking have been reviewed 2 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Various studies with rats, mostly employing chronic choice drinking paradigms [e.g. 36;37;28 ] showing positive effects of acamprosate on alcohol drinking have been reviewed 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In a 1 hr single bottle test, one injection of 10 mg/kg baclofen (but not higher or lower doses from 5–20 mg/kg) increased drinking and the resulting BAL 39 . However, multiple studies with different test parameters and subject populations including both mice and rats have shown that baclofen could either increase or decrease ethanol intake [for reviews, see 2;40 ]. Reasoning that enantiomer-specific effects could have contributed to this variability, Steve Boehm’s group showed that a peripheral injection of 10 mg/kg of the R(+) enantiomer deceased DID drinking and BAL in C57BL/6J male mice while the same dose of the S(-) enantiomer modestly increased ethanol intake without affecting BAL.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations